Frequent polymorphism in BCR exon b2 identified in BCR-ABL positive and negative individuals using fluorescent hybridization probes - Saußele, Susanne; Weißer, Andreas; Müller, Martin Christian; Emig, Michael; La Rosée, Paul; Paschka, Peter; Kuhn, Christian; Willer, Andreas; Hehlmann, Rüdiger; Hochhaus, Andreas (Leukemia, 2000)
Recently, a polymorphic base in exon 13 of the BCR gene (exon b2 of the major breakpoint cluster region) has been identified in the eighth position before the junctional region of BCR-ABL cDNA. Cytosine replaces thymidine; the corresponding triplets are AAT (T allele) and AAC (C allele), respectively, both coding for asparagine. Therefore, this polymorphism has no implication in the primary structure of BCR and BCR-ABL proteins. However, since the alteration is located close to the fusion region it may have a significant influence on the annealing of PCR primers, probes for real time PCR, and antisense oligonucleotides. We have developed a RT-PCR-based screening method to easily identify polymorphic BCR and BCR-ABL alleles in CML patients and normal individuals in order to estimate their frequency. After amplification from cDNA, a melting curve of a specific fluorogenic probe mapping to the 3′ end of BCR exon b2 and spanning the polymorphism readily discriminates between normal and polymorphic BCR and BCR-ABL alleles. This reporter probe is 3′ labeled with fluorescein and placed next to 5′ LC Red640-labeled anchor probes mapping to the 5′ ends of BCR exon b3 or ABL exon a2 so that resonance energy transfer occurs when the probes are hybridized (LightCycler technology). T and C alleles were discriminated by a melting temperature difference of the reporter probe of 3.2 K. We have investigated cDNAs derived from leukocytes from seven cell lines and a total of 229 individuals: normal donors, n = 15; BCR-ABL negative chronic myeloproliferative disorders, n = 30; BCR-ABL negative acute leukemias, n = 11; b2a2BCR-ABL positive CML, n = 93; and b3a2BCR-ABL positive CML, n = 80. The frequency of the C allele was 33.0% in BCR-ABL negative individuals, 30.6% in b2a2BCR-ABL, and 23.8% in b3a2BCR-ABL positive CML. In CML patients, 27.7% of BCR-ABL and 27.2% of BCR alleles had the C allele (NS). In total, 132 of 458 (28.8%) exons b2 of BCR or BCR-ABL alleles demonstrated this polymorphism. We conclude that a thymidine/cytosine replacement occurs frequently in BCR exon b2. Probes for real time quantitative RT-PCR should be designed not to map to the critical region in order to avoid underestimation of the number of BCR-ABL transcripts.
Gesehen am 13.04.2022